Effects of Different Resistance Training Systems on Muscular Strength and Hypertrophy in Resistance-Trained Older Women. Issue 2 (February 2018) - Ribeiro, Alex S.; Aguiar, Andreo F.; Schoenfeld, Brad J.; Nunes, João P.; Cavalcante, Edilaine F.; Cadore, Eduardo L.; Cyrino, Edilson S.
Abstract : Abstract: Ribeiro, AS, Aguiar, AF, Schoenfeld, BJ, Nunes, JP, Cavalcanti, EF, Cadore, EL, and Cyrino, ES. Effects of different resistance training systems on muscular strength and hypertrophy in resistance-trained older women. J Strength Cond Res 32(2): 545–553, 2018—The purpose of this study was to investigate the effect of resistance training (RT) performed in a pyramid (PR) vs. constant (CT) load system on muscular strength and hypertrophy in resistance-trained older women. Thirty-three older women (69.7 ± 5.9 years, 69.1 ± 15.0 kg, 156.6 ± 6.2 cm, and 28.1 ± 5.4 kg·m −2 ) were randomized into 2 groups: one that performed RT with a CT load ( n = 16) and another group that performed RT in an ascending PR fashion ( n = 17). Outcomes included 1 repetition maximum (RM) tests and assessment of skeletal muscle mass estimated by dual-energy X-ray absorptiometry. The study lasted 32 weeks, with 24 weeks dedicated to preconditioning and 8 weeks for the actual experiment. The RT program was conducted 3 d·wk −1 ; the CT consisted of 3 sets of 8–12RM with same load across sets, whereas the PR consisted of 3 sets of 12/10/8RM with incremental loads for each set. A significant ( p ⩽ 0.05) change from pretraining to posttraining was observed for chest press total strength (CT: pre = 122.8 ± 21.0 kg, post = 128.9 ± 21.4 kg, effect size [ES] = 0.28; PR: pre = 120.5 ± 22.8 kg, post = 125.8 ± 22.9 kg, ES = 0.24) and muscle mass (CT: pre = 21.4 ± 3.6 kg, post = 21.7 ± 3.5 kg, ES = 0.09; PR: pre = 20.9 ± 3.4 kg, post = 21.1 ± 3.4 kg, ES = 0.06) without differences between groups. Results suggest that both systems are effective to improve strength and muscle growth, but PR is not superior to CT for inducing improvements in previously trained older women.